Can blogging increase extroverts' satisfaction in the classroom? Lessons from multiple case studies. Issue 6 (17th August 2016) - Samuel-Azran, Tal; Ravid, Gilad
Abstract : In light of systematic evidence that extroverts are disadvantaged in the classroom, we examined whether an online environment assignment that builds on extroverts' character strengths can increase their overall course satisfaction. Based on previous studies demonstrating that extroverts are energized by feedback from outsiders, we asked 180 students to blog regarding classroom material with the aim of attracting maximum attention from strangers. The questionnaires completed at the beginning of the course confirmed that extroverts believed, significantly more so than introverts, that outsiders would be interested in what they have to say, illustrating the potential of such task. The questionnaires completed at the end of the course ( N = 109), however, revealed that participants expressed disappointment with their ability to attract attention to their blogs. Follow-up interviews revealed that students liked the nature of the assignment but not the platform. Most of them suggested using more extrovert-friendly platforms in the future.